Black American Men's Treatment Experiences in Mental Health Court: a Phenomenological Analysis - Stare, Bryan G. (Journal of addictions & offender counseling, 2019)
In this qualitative study, the authors examined young adult Black American men's perceptions of treatment in mental health diversion programs. Findings included 3 themes: helpful treatment factors, cognitive dissonance, and treatment barriers. The authors explore counseling competency and advocacy considerations for judicial settings.